2016
DOI: 10.1073/pnas.1615316113
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of recognition of farnesylated and methylated KRAS4b by PDEδ

Abstract: Farnesylation and carboxymethylation of KRAS4b (Kirsten rat sarcoma isoform 4b) are essential for its interaction with the plasma membrane where KRAS-mediated signaling events occur. Phosphodiesterase-δ (PDEδ) binds to KRAS4b and plays an important role in targeting it to cellular membranes. We solved structures of human farnesylated–methylated KRAS4b in complex with PDEδ in two different crystal forms. In these structures, the interaction is driven by the C-terminal amino acids together with the farnesylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
208
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(221 citation statements)
references
References 62 publications
13
208
0
Order By: Relevance
“…However, it is still unclear to what extent designing drugs to inhibit the interaction of K-Ras4B with PDEδ would accomplish this goal. The recent structure [82] coupled with earlier observations [83] and modeling suggest that PDEδ may be able to bind other depalmitoylated isoforms, and geranyl-geranylated K-Ras is also a PDEδ substrate; not only farnesylated K-Ras. CaM’s interaction with K-Ras4B and its role in KRAS -driven cancers have long been considered an option [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear to what extent designing drugs to inhibit the interaction of K-Ras4B with PDEδ would accomplish this goal. The recent structure [82] coupled with earlier observations [83] and modeling suggest that PDEδ may be able to bind other depalmitoylated isoforms, and geranyl-geranylated K-Ras is also a PDEδ substrate; not only farnesylated K-Ras. CaM’s interaction with K-Ras4B and its role in KRAS -driven cancers have long been considered an option [5].…”
Section: Discussionmentioning
confidence: 99%
“…Full Length KRas4b was solvated and equilibrated for 20 ns using NAMD 2.11 molecular Dynamics software package [17] and was later found to be nearly identical to the recently published full-length structure of KRas4b. [18]…”
Section: Methodsmentioning
confidence: 99%
“…Our structural work on full-length KRAS4b in complex with PDEδ showed that unlike Rho and Rab GDIs that interact with both prenylated lipid and switch regions of G-domain, PDEδ only interacts with the C-terminal amino acids together with the farnesylated and methylated C185 of KRAS4b (Dharmaiah et al, 2016). Structure-based sequence analysis identified a 5-amino acid long sequence motif (Lys-Ser-Lys-Thr-Lys) in KRAS4b that may enable PDEδ to bind to both farnesylated as well as geranylgeranylated KRAS4b.…”
Section: Ras Proteins In the Membranementioning
confidence: 99%